Association of HLA type with pseudoexfoliation of the lens capsule. Issue 5 (May 1996) - FitzSimon, J S; Mulvihill, A; Kennedy, S; Finch, A; Collum, L M; Eustace, P
Abstract : AIMS/BACKGROUND: To identify an HLA association with pseudoexfoliation of the lens capsule to support the hypothesis that there is a genetic predisposition to pseudoexfoliation. A randomised trial would be ideal for establishing a relation but is more costly and time consuming to conduct. Case-control studies provide an alternative method of establishing a relation. METHODS: The study group comprised 128 subjects who presented to a major eye centre with pseudoexfoliation. Data from blood donors representative of the population of Ireland were used to form a control group. RESULTS: An HLA association with pseudoexfoliation is identified for 14 antigens. Eleven antigens (HLA A1, A33, B8, B47, B51, B53, B57, B62, DR3, DR12, and DR13) are significantly more common in the pseudoexfoliation group while three antigens (HLA B12, B17, and DR2) are significantly less common. Four HLA antigens are strongly associated, with odds ratios of over 7.5. CONCLUSION: The strength of this HLA association is supportive evidence for a genetic component to the development of pseudoexfoliation of the lens capsule.